2019
DOI: 10.1111/imcb.12229
|View full text |Cite
|
Sign up to set email alerts
|

The anthelmintic drug praziquantel promotes human Tr1 differentiation

Abstract: Praziquantel (PZQ) is an anthelminthic human and veterinary drug used to treat trematode and cestode worms. Changes in immune responses have been demonstrated in humans following curative PZQ treatment of schistosome infections. These changes have been attributed to the removal of immunosupressive worms and immune responses to parasite antigens exposed from dying worms. To date, there has been no study investigating the potential direct effect of PZQ on the host immune cells. Herein, we analyzed the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Conditions such as HIV (Joseph et al, 2004b), coinfection with whipworm (our unpublished data show increased Schistosoma egg-induced hepatopathology during co-infection with Trichuris), malnutrition (Scrimshaw and SanGiovanni, 1997), and others can affect vaccine efficacy. PZQ treatment, discounting the release of parasite antigens, may intrinsically be immunomodulatory (Eyoh et al, 2019). To our knowledge, this study is the first to report the cellular immune response in a non-human primate model of schistosomiasis using multiple trickle infections and subsequent chemotherapy with PZQ.…”
Section: Discussionmentioning
confidence: 92%
“…Conditions such as HIV (Joseph et al, 2004b), coinfection with whipworm (our unpublished data show increased Schistosoma egg-induced hepatopathology during co-infection with Trichuris), malnutrition (Scrimshaw and SanGiovanni, 1997), and others can affect vaccine efficacy. PZQ treatment, discounting the release of parasite antigens, may intrinsically be immunomodulatory (Eyoh et al, 2019). To our knowledge, this study is the first to report the cellular immune response in a non-human primate model of schistosomiasis using multiple trickle infections and subsequent chemotherapy with PZQ.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, two subsets of Foxp3 − Tregs have been discovered with suppressor functions: type 1 Treg (Tr1) and Th3 cells differentiate from peripheral naive CD4 + T cells ( 16 , 23 ). As opposed to tTregs, Th3 and Tr1 suppressive properties are contact independent and is largely relying on cytokines including IL-10 and transforming growth factor- β (TGF- β ) ( 24 ) ( Figure 2 ).…”
Section: Origin Phenotype and Markersmentioning
confidence: 99%
“…The discovery of LAG3 and CD49b expressed on both murine and human memory CD4 + Tr1 cells enabled the isolation and characterization of Tr1 populations from peripheral blood of healthy donors (10). Since then, many other studies confirmed the expression of these proteins on murine (21)(22)(23)(24)(25)(26)(27)(28)(29), non-human primate (30) and human (18,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) Tr1 cell populations.…”
Section: Biological Characterization Of Human Tr1 Cells Phenotypementioning
confidence: 99%